2017
DOI: 10.1364/oe.25.024437
|View full text |Cite
|
Sign up to set email alerts
|

Optomechanical properties of GaAs/AlAs micropillar resonators operating in the 18 GHz range

Abstract: Recent experiments demonstrated that GaAs/AlAs based micropillar cavities are promising systems for quantum optomechanics, allowing the simultaneous three-dimensional confinement of nearinfrared photons and acoustic phonons in the 18-100 GHz range. Here, we investigate through numerical simulations the optomechanical properties of this new platform. We evidence how the Poisson's ratio and semiconductor/vacuum boundary conditions lead to very distinct features in the mechanical and optical three dimensional con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Additionally, the realization of high-frequency optomechanical systems is highly desirable for metrology applications [5] and for ultrafast information processing [6,7]. As part of this pursuit, micropillar resonators operating at ultrahigh frequencies (greater than 10 GHz) and presenting strong optomechanical interactions and state-of-the-art Q-frequency products have been reported recently [8,9]. This frequency range, however, comes together with critical challenges.…”
mentioning
confidence: 99%
“…Additionally, the realization of high-frequency optomechanical systems is highly desirable for metrology applications [5] and for ultrafast information processing [6,7]. As part of this pursuit, micropillar resonators operating at ultrahigh frequencies (greater than 10 GHz) and presenting strong optomechanical interactions and state-of-the-art Q-frequency products have been reported recently [8,9]. This frequency range, however, comes together with critical challenges.…”
mentioning
confidence: 99%
“…Moreover, a phononic ridge can be used to excite high QF surface phonons, which can then couple with external photons. Very recently, Anguiano et al [63] and Lamberti et al [64] demonstrated the confinement of both phonons and photons with strong optomechanic coupling in a composite multilayered GaAs/AlAs micopillar. The composite pillar-based system would be a promising structure for observing quantum optomechanic phenomena, and even for integration into a biosensing platform for instance, to increase device sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the vertical direction, the resonant cavity confinement leads to an exponentially decaying envelope of the optical mode in both DBRs. In the radial direction, the refractive index contrast between the semiconductor materials and vacuum leads to an additional in-plane confinement of the mode with a Bessel -type envelope [34][35][36] much like for an optical fiber. To probe the Brillouin spectrum of individual micropillars, an incident laser beam (mode hop -free cw Ti:Sa laser M2 SolsTiS) resonant with the fundamental optical micropillar mode is focused to a spot size of roughly 10µm (FWHM) on the sample surface and centered on a pillar.…”
Section: Brillouin Spectroscopy On Micropillarsmentioning
confidence: 99%